Legal Implications of Teachers and Principals’ Management of Negligent Issues in Public Senior Secondary Schools in Port Harcourt Metropolis - Koko, M. N (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examined the legal implications of teachers and principals’ management of negligent issues in public senior secondary schools in Port Harcourt Metropolis. Two objectives, two research questions and two hypotheses guided the study. The study adopted a descriptive survey design. The total population of the study was 1,985 individuals, consisting 1,943 teachers and 42 principals of the public senior secondary schools in Port Harcourt Metropolis. The sample of the study was 200 respondents comprising 15 principals and 185 teachers. The instrument for the study was self-structured questionnaire titled: “Legal Implications of Teachers and Principals Management of Negligent Issues Questionnaire” which was based on a 4-point rating scale of Strongly Agree, Agree, Disagree, and Strongly Disagree. The instrument was face and content validated by two experts from Measurement and Evaluation, and Department of Educational Management, and tested for reliability using Cronbach Alpha internal consistency method, which yielded an average 0.84. The research questions were answered with mean and standard deviation while the hypotheses were tested at 0.05 significant level using the t-test. The study revealed that negligent issues are inadequately managed in secondary schools, largely due to the absence of clear safety policies. It also revealed no significant difference between teachers and principals regarding awareness of the implications of negligence, largely due to lack of legal literacy training. Implications of these findings suggest a need for clearer safety guidelines, targeted legal training, and stronger institutional frameworks to effectively manage negligence and ensure a safer school environment.